Survey of Environmental Quality in Three Springs of an Integral Protection Conservation Unit in Manaus-Amazonas - Lima, Andréia Vieira; Santos, Janilce Lemos dos; Baggio, Priscilla Maia; Alencar, David Barbosa de; Lopes, Gisele de Freitas (International Journal of Advanced Engineering Research and Science, 2019)
Springs are characterized as groundwater environmental hydro systems, in which they occur temporarily or perennially, and are present in natural and anthropic areas. The present study analyzed the environmental quality in three springs located in an integral protection conservation unit in the city of Manaus, Amazonas. To characterize the study area, there was georeferencing of images from the Google Earth software in the ArcGIS and Qgis programs, the survey of the environmental quality of the springs was performed through the methodological procedure of macroscopic analysis of 12 physicochemical and biological parameters and, the classification of spring conditions by the sum of the degree of criticality of each item evaluated, resulting in a score. It was verified that two springs were classified as “bad” and “bad”, respectively, and only one spring was rated “optimal” for its environmental condition, due to its degree of distance from the urbanization limit. The results revealed a warning sign regarding the neglect of the environmental agencies regarding the protection of existing natural resources, consequently, indicate the need to carry out an inspection regarding compliance with the established laws for the preservation of water bodies and riparian forests.